A journey to a cold seep: How scientists study methane in the Arctic ocean: A paired teaching lesson plan - Mohadjer, Solmaz; Aune, Vibeke; Panieri, Giuliana; Oddone, Davide (Septentrio Educational, 2023)
Focus:Where are and what happens at cold seeps and how scientists study them.Learning objectives:After this lesson, students should be able to:• Relate different datasets by observing and describing scientific maps• Differentiate between carbon dioxide and methane gas• Clarify misconceptions about greenhouse gas• Explain what cold seeps are and why most gas/methane hydratesoccur at continental margins• Describe some of the methods scientists use to locate and studymethane/gas hydratesPrerequisites:Prior to this lesson, students should be familiar with understanding maps, molecular structure and bonding, and the greenhouse effect and gases.Key words:Arctic Ocean, Methane, Carbon Dioxide, Gas Hydrate, Cold Seep, Greenhouse Gases.